1993
DOI: 10.1254/jjp.62.215
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ischemic Myocardial Dysfunction by Nisoldipine in Relation to Its Coronary Vasodilating Action

Abstract: ABSTRACT-We examined the protective activity of fructose l,6-bisphosphate (FBP) on mortality and delayed hippocampal cell death induced by transient cerebral ischemia in the Mongolian gerbil. Forebrain ischemia was produced by bilaterally occluding the common carotid arteries for 15 min using micro aneurysm clips; then the blood supply to the brain was restored. The number of survivors was counted for 8 days, and the histopathological damage in the CAI region of the hippocampus was scored according to the semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In Langendorff-perfused rat hearts, FDP was shown to preserve high-energy metabolites during anoxia, restore myocardial metabolism and contractility during reperfusion (9), and improve myocardial efficiency under well-perfused and well-oxygenated conditions (22). Improvement in tissue metabolic state during metabolic stress has been reported in a number of other tissue types, including kidney (1), liver (19), brain (26), erythrocytes (8), smooth muscle (5), and intestine (24). Many of these effects were likely due to FDP entering cells, but also due to the known calcium chelating activity of FDP (see Ref.…”
Section: Discussionmentioning
confidence: 98%
“…In Langendorff-perfused rat hearts, FDP was shown to preserve high-energy metabolites during anoxia, restore myocardial metabolism and contractility during reperfusion (9), and improve myocardial efficiency under well-perfused and well-oxygenated conditions (22). Improvement in tissue metabolic state during metabolic stress has been reported in a number of other tissue types, including kidney (1), liver (19), brain (26), erythrocytes (8), smooth muscle (5), and intestine (24). Many of these effects were likely due to FDP entering cells, but also due to the known calcium chelating activity of FDP (see Ref.…”
Section: Discussionmentioning
confidence: 98%
“…During the past twenty years of brain research post-ischemic outcome improvements by FBP have been found by some to be dramatic, by others to be simply modest[6,11,12,19-21,31,35,39], and by a smaller number to be completely nonexistent[10,22,23]. FBP studies showing neuroprotection pose a formidable intellectual challenge: do improved outcomes come from important, already known injurious mechanisms that are typically focused upon, such as glutamate excitotoxicity, calcium overload, acidosis, oxygen radicals, PARP-1 activation, apoptosis, etc?…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic neuroprotection from FBP administration was subsequently demonstrated in animal experiments[6,12,21,35], cell culture studies[11,19,20,31,39], as well as in a brain slice study by us[3]. Our previous investigation of FBP neuroprotection used 31 P and 1 H ex vivo NMR spectroscopy in a horizontal 4.7 Tesla wide-bore spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…During the twenty years that followed his initial FBP experiments, many others, too many to report, studied FBP use in hypoxia, ischemia, and/or oxidative stress. Post-ischemic outcome improvements were found by some to be dramatic, by others to be simply modest [3840], and by a smaller number to be completely nonexistent [4143]. Although many important, significant, animal investigations of FBP’s protective and therapeutic actions have been carried out since the 1980’s, and although much has also been learned about molecular mechanisms of hypoxic/ischemic injury, the mechanisms by which FBP protects various tissues were never clearly established, and FBP administration never became part of routine clinical care.…”
Section: Investigations Of Two Metabolites As Treatments In Oxidatmentioning
confidence: 99%